INTERDISCIPLINARY CONNECTIONS IN TEACHING ENGLISH TO CADETS OF ECONOMIC SPECIALITIES - Oksana P. Bykonia; Olena B. Shenderuk (Alfred Nobel University Publisher, 2022)
The article deals with the peculiarities of teaching cadets of economic specialties English for Specific Purposes, taking into account the interdisciplinary links. It is pointed out that teaching a foreign language to cadets at the Academy of the State Penitentiary Service must be on the basis of methodological approaches and peculiarities of unified entrance exam in a foreign language for admission to study for obtaining a master's degree in the fields of knowledge 05 "Social and behavioral sciences". In the article the authors analyze the latest research on teaching future specialists foreign languages on the basis of such methodological approaches as system, activity, competence, aspect, context approach and others. In the context of the study, the authors determine that mastering English communicative competence in professional communication by the cadets should take into account interdisciplinary links, especially working together with the specialized departments. The authors indicate that teaching cadets of economic specialties English for Specific Purposes should be implemented on the basis of systematic, competency-based, professionally-oriented and interdisciplinary approaches. The aim of the article is to determine the features of teaching cadets of economic specialties English for Specific Purposes on the basis of those approaches with taking into account interdisciplinary links. In the article the authors give the analysis the disciplines that the four-year cadets of economic specialties study at the Academy of the State Penitentiary Service. They state that the acquisition of professional English communicative competence is possible in case of taking into account the professional themes connected with the disciplines studied by future economists in the Academy. The requirements of the unified entrance exam in a foreign language are considered while developing the tasks and exercises to teach cadets of economic specialties English. The tasks for developing English lexical and grammatical competences and competence in reading are included.